Copy Number Variation at the APOL1 Locus. - Rupam Ruchi; Giulio Genovese; Jessica Lee; Victoria T Charoonratana; Andrea J Bernhardy; Seth L Alper; Jeffrey B Kopp; Ravi Thadhani; David J Friedman; Martin R Pollak (PLoS ONE, 2015)
Two coding variants in the APOL1 gene (G1 and G2) explain most of the high rate of kidney disease in African Americans. APOL1-associated kidney disease risk inheritance follows an autosomal recessive pattern: The relative risk of kidney disease associated with inheritance of two high-risk variants is 7-30 fold, depending on the specific kidney phenotype. We wished to determine if the variability in phenotype might in part reflect structural differences in APOL1 gene. We analyzed sequence coverage from 1000 Genomes Project Phase 3 samples as well as exome sequencing data from African American kidney disease cases for copy number variation. 8 samples sequenced in the 1000 Genomes Project showed increased coverage over a ~100kb region that includes APOL2, APOL1 and part of MYH9, suggesting the presence of APOL1 copy number greater than 2. We reasoned that such duplications should be enriched in apparent G1 heterozygotes with kidney disease. Using a PCR-based assay, we observed the presence of this duplication in additional samples from apparent G0G1 or G0G2 individuals. The frequency of this APOL1 duplication was compared among cases (n = 123) and controls (n = 255) with apparent G0G1 heterozygosity. The presence of APOL1 duplication was observed in 4.06% of cases and 0.78% controls, preliminary evidence that this APOL1 duplication may alter susceptibility to kidney disease (p = 0.03). Taqman-based copy number assays confirmed the presence of 3 APOL1 copies in individuals positive for this specific duplication by PCR assay, but also identified a small number of individuals with additional APOL1 copies of presumably different structure. These observations motivate further studies to better assess the contribution of APOL1 copy number on kidney disease risk and on APOL1 function. Investigators and clinicians genotyping APOL1 should also consider whether the particular genotyping platform used is subject to technical errors when more than two copies of APOL1 are present.